Capturing emotional experience of children and adolescents with intellectual disabilities using the experience sampling method - Zurbriggen, Carmen L. A.; Audeoud, Mireille; Lütolf, Matthias; Stöcker, Anne; Schaub, Simone (Frontiers in Education, 2026)
BackgroundWhile the Experience Sampling Method (ESM) is particularly suitable for assessing subjective views and inner phenomena such as emotional experience, it is still rarely used in research involving individuals with intellectual disabilities (ID)—especially children and adolescents. In an innovative attempt, the present study aimed to develop an ESM survey incorporating self-report measures to assess the emotional experience of children and adolescents with ID, and to examine the feasibility of this approach.MethodsWe developed an ESM survey design through a stepwise, participatory procedure guided by predefined criteria. To evaluate feasibility, we conducted a pilot study over an 8-week period involving 9 children and adolescents with mild to moderate ID (aged 5–15) and interviewed both the participants and their parents.ResultsThe findings revealed intraindividual variability in participants’ emotional experience and interindividual variation in their assessment of different situations and activities. Evaluation meetings with participants and their parents supported the feasibility of the ESM approach.ConclusionBased on our pilot study, it can be cautiously concluded that the adapted ESM survey design is suitable for assessing the emotional experience of children and adolescents with mild to moderate ID. Future studies with larger sample sizes and more rigorous approaches are needed to further develop this approach.